(untitled) (Journal of Namibian Studies : History Politics Culture, 2022)
Factors that influence the participation of university students in physical-sports activities were identified and classified. Methodologically it was a mixed study with a non-experimental, cross-sectional, correlational, and descriptive design. For data collection and analysis, a systematic review was carried out on the reasons why students participate in physical-sports activities and then the MICMAC technique was applied, for which the help of experts was sought who, with their collective reflection, allowed the structural analysis to be carried out. The results yielded eleven factors that were directly classified as key. It is concluded that students may be motivated by competition, the desire to keep fit, the desire to socialize, or the desire to represent their school or team. In addition, the availability of resources such as appropriate sports facilities, coaches, and equipment can be an important factor in a student’s decision to participate in sports activities.